2016
DOI: 10.1002/osp4.79
|View full text |Cite
|
Sign up to set email alerts
|

The association between parental separation during childhood and obesity in adulthood: a Danish twin study

Abstract: SummaryObjectiveThe purpose of this study was to examine if parental separation during childhood is associated with obesity in adulthood.MethodsA co‐twin case–control study of 146 adult same‐sexed twin pairs with discordant body mass index (BMI) (i.e. one of the twins should have a BMI of 20–25 kg/m2, and the co‐twin's BMI ≥ 30 kg/m2) was selected from Danish Twin Registry (DTR). In total of 236 eligible twin individuals participated in the study. Childhood parental separation (defined as separation from one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…We include poverty in this list of adverse experiences as has been recently advocated 13 . Growing evidence indicates that adverse childhood experiences, such as maltreatment 1416 , parental death or separation 1719 , and poverty 20,21 , are important risk factors for later obesity. Childhood mental and substance use disorders are another common set of challenges that have been linked to obesity.…”
Section: Introductionmentioning
confidence: 99%
“…We include poverty in this list of adverse experiences as has been recently advocated 13 . Growing evidence indicates that adverse childhood experiences, such as maltreatment 1416 , parental death or separation 1719 , and poverty 20,21 , are important risk factors for later obesity. Childhood mental and substance use disorders are another common set of challenges that have been linked to obesity.…”
Section: Introductionmentioning
confidence: 99%
“…early risk of the health consequences of obesity than other measures of obesity, such as waist circumference and BMI 25. Many studies have shown that obesity in adult age could be caused by various psychological risk factors during childhood, such as maltreatment, separation of parents or their death, and mental disorders, e.g., early onset major depressive syndrome, binge-eating disorders, and tobacco use [26][27][28][29][30][31][32][33][34][35][36]. …”
mentioning
confidence: 99%
“…Participants who reported contact disruption with parents were also asked about the severity of the disruption. These items were adapted from Petersen et al (2016).…”
Section: Methodsmentioning
confidence: 99%